(3QO GdeMJGQ Ydi GdOQ GdeNJGQs - (3GHf YGHOjf, eMeO Cejf Hf YeQ Hf YHO GdYRjR, (B1252 (3g`s
(3ChdgG (B:s
(3deG aQZ EdN HjGf ddefGSHI Hjf LedI eG JbOe hLedI eG jCJj eY HjGf GdefGSHI Hjf NUhU Gdhba hGdHjY hGdeQGO HGdYHGOGJs
(3BNQgG (B:s
(3hPcQ GdRjdYj gfGc ajeG dh fbU GdeZUhH GdQHhj jNjQ GdeGdc Hjf Cf jeSc GdYjf hdG jQLY Ydi GdZGUH HTjA hHjf Cf jSdegG hjVef eKdgG Ch bjeJgG dCf JVejf GdfbU eJYPQ dCfg jDOj Edi GdQHG GfJgi hHg Ydes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 42s
(3eYLe GdeDdajf (B3 / 145s
(3EjVGM Gdecfhf (B1 / 556s
(3gOjI GdYGQajf (B2 / 367s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs